Exact solutions and Lattice Boltszmann modeling for shallow water equations - Sara Zergani, 1984-; Zainal Abdul Aziz, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2012